Elliptic flow of charged particles in Pb-Pb collisions at √sNN=2.76 TeV - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (Physical review letters, 2010)
We report the first measurement of charged particle elliptic flow in Pb-Pb collisions at √sNN=2.76 TeV with the ALICE detector at the CERN Large Hadron Collider. The measurement is performed in the central pseudorapidity region (|η|<0.8) and transverse momentum range 0.2<pt<5.0 GeV/c. The elliptic flow signal v2, measured using the 4-particle correlation method, averaged over transverse momentum and pseudorapidity is 0.087±0.002(stat)±0.003(syst) in the 40%-50% centrality class. The differential elliptic flow v2(pt) reaches a maximum of 0.2 near pt=3 GeV/c. Compared to RHIC Au-Au collisions at √sNN=200 GeV, the elliptic flow increases by about 30%. Some hydrodynamic model predictions which include viscous corrections are in agreement with the observed increase.